Pengaruh Persepsi Manajer Atas Informasi Akuntansi Terhadap Keberhasilan Mengelola UKM Di Sidoarjo - Chotimah, Nurul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is firstly, to find out whether the attention to accounting information has positive influence to the success of managing small and medium enterprise in Sidoarjo. Secondly, to find out whether the understanding of accounting information has positive influence to the success of managing small and medium enterprise in Sidoarjo. Finally, to find out whether the memory of accounting information has positive information to the success of managing small and medium enterprise in Sidoarjo.This research uses quantitative research type with independent variables: attention, understanding, and memory. The dependent variable is the success of managing small and medium enterprise in Sidoarjo. The sample collection technique is the saturated Jurnal Ilmu & Riset Akuntansi Vol. 3 No. 10 (2014)2sampling by using multiple linear regression analysis with computerized instrument SPSS 17.0. Based on the result of t-test it has been found that the attention on accounting information (X1) can give significant influence to the success of managing small and medium enterprise (Y). The understanding on accounting information (X2) can give positive and significant influence to the success of managing small and medium enterprise (Y). The result of t-test for memory on accounting information (X3) can give positive and significant influence to the success of managing small and medium enterprise (Y).Keywords: Managerâs Perception, Accounting Information, Small and Medium Enterprise